SIRT1 upregulation protects against liver injury induced by a HFD through inhibiting CD36 and the NF-κB pathway in mouse kupffer cells - Niu, Bailin (Mol Med Rep, 2018)
Sirtuin 1 (SIRT1) is an NAD(+)-dependent deacetylase, and a critical regulator in various metabolic processes, such as non-alcoholic fatty liver disease (NAFLD). The present study aimed to investigate whether activating SIRT1 could modulate the CD36 and nuclear factor (NF)-κB pathways to protect against liver injury induced by a high-fat diet (HFD) in mice. A mouse NAFLD model was established by administration of a HFD for 8 weeks. During the last 4 weeks, SRT1720, a specific SIRT1 activator, was added daily to the HFD feed. The hepatic morphological structure was observed using hematoxylin and eosin staining, and the ultrastructures in the liver tissue were observed using transmission electron microscopy. Protein expression of SIRT1, CD36 and P65 in liver tissues was detected by immunohistochemistry. Kupffer cells (KCs) from the livers of the mouse models were isolated to determine the mRNA and protein expression of SIRT1, CD36 and P65. SIRT1 activation attenuated the HFD-induced liver injury and significantly reduced the body weight and the levels of alanine transaminase, aspartate aminotransferase, triglyceride, tumor necrosis factor-α and interleukin-6. We observed an increased expression of SIRT1 in the liver tissues from the HFD+SRT1720 group compared with the HFD group. Simultaneously, the expression of CD36 and P65 in the liver tissues was downregulated in the HFD+SRT1720 group. The mRNA and protein expression of SIRT1 was elevated in the HFD+SRT1720 group, whereas the mRNA and protein expression of CD36 and P65 in KCs was significantly decreased in the HFD+SRT1720 group. The present study demonstrated that SIRT1 activation attenuated HFD-induced liver steatosis and inflammation by inhibiting CD36 expression and the NF-κB signaling pathway.